Control interno y proceso logístico en la municipalidad provincial de Loreto Nauta, 2021 - Soria Chapiama, Eliseo (2022)
The objective of the research was to determine the relationship between internal control and the logistics process in the Provincial Municipality of Loreto Nauta, 2021. The methodology used for the development of the research was of an applied type, with a correlational descriptive level accompanied by a non-experimental design. . A population and sample of 37 employees from the logistics area were taken, to whom the survey was applied as a technique and the question questionnaire as an instrument. Among the results, it was possible to determine the internal control in the Provincial Municipality of Loreto Nauta is regular, because a commitment to integrity and ethical values is rarely evidenced at all hierarchical levels, likewise, in the processes of the entity always estimates the importance and relevance of the risks, but only sometimes corrective decisions are made and implemented, finally, control activities are almost never developed according to the objectives established in the entity. On the other hand, the logistical processes in said institution are regular, since only sometimes are quote requests sent to the supplier companies, while a report is almost never made with the quotes made, likewise, the registration and respective control of the delivered goods, lastly, verification of the origin of the surplus goods is almost never carried out. In conclusion, it was determined that there is a considerable and significant relationship between internal control and the logistics process in the Provincial Municipality of Loreto Nauta in the year 2021, contrasted by a correlation of 0.882.